Virtual reality lifeguarding scenarios as a potential training solution for pool lifeguards. (April 2023) - Lim, David; Wiggins, Mark; Porte, Meredith; Bayl-Smith, Piers; Curby, Kim M.; Olsen, Kirk N.; Taylor, Melanie
Abstract: Background: Ensuring that pool lifeguards develop the skills necessary to detect drowning victims is challenging given that these situations are relatively rare, unpredictable and are difficult to simulate accurately and safely. Virtual reality potentially provides a safe and ecologically valid approach to training since it offers a near-to-real visual experience, together with the opportunity to practice task-related skills and receive feedback. As a prelude to the development of a training intervention, the aim of this research was to establish the construct validity of virtual reality drowning detection tasks. Method: Using a repeated measures design, a total of 38 qualified lifeguards and 33 non-lifeguards completed 13 min and 23 min simulated drowning detection tasks that were intended to reflect different levels of sustained attention. During the simulated tasks, participants were asked to monitor a virtual pool and identify any drowning targets with accuracy, response latency, and dwell time recorded. Results: During the simulated scenarios, pool lifeguards detected drowning targets more frequently and spent less time than non-lifeguards fixating on the drowning target prior to the drowning onset. No significant differences in response latency were evident between lifeguards and non-lifeguards nor for first fixations on the drowning target. Conclusion: The results provide support for the construct validity of virtual reality lifeguarding scenarios, thereby providing the basis for their development and introduction as a potential training approach for developing and maintaining performance in lifeguarding and drowning detection. Application: This research provides support for the construct validity of virtual reality simulations as a potential training tool, enabling improvements in the fidelity of training solutions to improve pool lifeguard competency in drowning detection. Highlights: Virtual reality offers an opportunity to develop lifeguarding skills in more environments that embody greater realism. Lifeguards recorded greater accuracy than non-lifeguards in detecting drowning victims during virtual scenarios. No differences were evident in response latency for drowning detection between lifeguards and non-lifeguards. Lifeguards recorded a lower dwell time on victims prior to drowning. A learning effect associated with the presentation of scenarios suggest that they can be employed for training purposes. Abstract : The capacity to detect drowning swimmers accurately and rapidly was assessed over extended periods using a drowning detection task that incorporated a virtual simulation of an aquatic pool. Pool lifeguards detected drowning targets more frequently than non-lifeguards in virtual drowning detection tasks.